Handoffs in the Intensive Care Unit: Are Off Hours a Vulnerable Time?. (March 2017) - Hochman, Beth R.; Barry, Mark E.; Lane-Fall, Meghan B.; Allen, Steven R.; Holena, Daniel N.; Smith, Brian P.; Kaplan, Lewis J.; Pascual, Jose L.
Operating room (OR) to intensive care unit (ICU) handoffs are complex and known to be associated with adverse events and patient harm. The authors hypothesized that handoff quality diminishes during nights/weekends and that bedside handoff practices are similar between ICUs of the same health system. Bedside OR-to-ICU handoffs were directly observed in 2 surgical ICUs with different patient volumes. Handoff quality measures were compared within the ICUs on weekdays versus nights/weekends as well as between the high- and moderate-volume ICUs. In the high-volume ICU, transmitter delivery scores were significantly better during off hours, while other measures were not different. High-volume ICU scores were consistently better than those in the moderate-volume ICU. Bedside handoff practices are not worse during off hours and may be better in ICUs used to a higher patient volume. Specific handoff protocols merit evaluation and training to ensure consistent practices in different ICU models and at different times.